Bangladesh : Reducing Emissions from Baby-Taxis in Dhaka - World Bank (Washington, DC, 2014)
The program, "Reducing Emissions from Baby-Taxis in Dhaka," included the education of commercial two-stroke engine three-wheel vehicle drivers and owners through mechanics training, a baby-taxi "auto clinic," meetings, dissemination of information, and informational meetings with auto mechanics and gasoline station owners who come in contact with vehicle drivers on a regular basis. The activity also sought to restructure the market for lubricants through both private voluntary action and government policy reform. To this end, the following activities were undertaken: Quantifying the impact of the use of excess inferior quality lubricant on emissions from baby-taxis; Training of mechanics servicing baby-taxis; Holding an auto clinic to demonstrate to the drivers the merit of changing their behavioral pattern with respect to the use of lube oil and vehicle maintenance; Consensus-building within the downstream petroleum sector on a ban on the; sale of straight mineral oil at gasoline stations; Other awareness-raising and dissemination activities to educate the drivers and the public on what affects vehicle emissions.